Evolution Characteristics of Coal Pore Structure with Nitrogen Hydraulic Composite Transformation - Huang, Juan; Yu, Wanying; Wang, Xinman; Wang, Shuaiqi; Liu, Yuanyuan (International Journal of Natural Resources and Environmental Studies, 2025)
China has abundant coalbed methane resources, comparable to conventional natural gas, with huge development potential. However, low-permeability and low-pressure coal reservoirs are widely developed, and single well production is generally low. Nitrogen hydraulic composite transformation is a potential technology to break through the efficient development of coalbed methane in low-permeability and low-pressure coal reservoirs. In order to study the influence of nitrogen hydraulic composite action on the evolution characteristics of pore and fracture structure in coal reservoirs, the Gaohe No. 3 coal in Lu'an mining area was taken as the research object. A nitrogen hydraulic composite transformation experimental device was built to carry out nitrogen transformation and nitrogen hydraulic composite transformation related experiments. The original coal samples and the coal samples modified by three methods were compared and analyzed through high-pressure mercury injection experiments to characterize the pore structure characteristics of the coal samples in the study area. The conclusion is as follows: The nitrogen hydraulic composite transformation in the Lu'an mining area has the effect of expanding and increasing the capacity of pores, causing the expansion and connectivity of transitionpores in coal to transform into large, medium, and micro cracks. The pore volume in the stage of pore size below 2nm is smaller after nitrogen and nitrogen hydraulic composite transformation, while the pore volume in the stage of pore size above 2nm increases; The improvement effect of pores after nitrogen transformation is relatively significant, and the pores are further improved after nitrogen hydraulic composite transformation.